Developing the SFBC Approach Individual Counseling Clinical Supervision Instrument in Senior High Schools - Ach. Sudrajad Nurismawan; Muslihati; M. Ramli (Universitas Mercu Buana Yogyakarta, 2025)
Based on the researchers' initial study at four high schools in the city of Surabaya, the researchers found that counseling supervision instruments in schools tend not to have been developed scientifically and are not optimal enough to be used in supervising individual counseling implementation indicators. Therefore, through the Borg and Gall development model, this study intends to develop a credible and accurate individual counseling clinical supervision instrument with a Solution-Focused Brief Counseling (SFBC) approach. Validation results from two counseling experts, three high school counselors, a readability test in focus group discussions, and a limited trial of counseling supervision practices involving five different high school counselors. It was found that individual counseling clinical supervision instruments covering planning and practice aspects met three criteria of acceptability (accuracy, usefulness, and practicality), while in the readability test, it was in a good category with an average score of 82%, with a sufficient validity level of > 0.754 and reliability 0.630 and 0.681 which means good. So that this product can be used by senior counselors to assist them in implementing individual counseling clinical supervision in schools